2018
DOI: 10.1039/c8ra01447g
|View full text |Cite
|
Sign up to set email alerts
|

Switching the optical and electrical properties of carbon nanotube hybrid films using a photoresponsive dispersant as a dopant

Abstract: The light-induced switching of the optical and electrical properties of single-walled carbon nanotubes (SWCNTs) was demonstrated following hybridisation with an azobenzene-based photoresponsive dispersant in solid film. The resultant SWCNT/photoresponsive dispersant hybrid film showed switching of absorbance in the near-infrared region by the irradiation of UV and visible lights, which was caused by the change of the doping ability of the dispersant to SWCNT. In addition, the switching of the electrical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Given that polymers are generally insulator [22], this thinning of the polymer shield over the CNTs facilitates the movement of charge carriers in the localized domains of the polyurethane network within the film [22], manifesting a promising light induced electrical photo-response and switching characteristics. Jintoku et al [9] reported on SWCNT, graphene hybrid films of having better absorbance by controlling the intensity and irradiation time of UV light and are switchable after visible light irradiation and thermal treatment, making them potential candidates for optoelectronic devices and sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that polymers are generally insulator [22], this thinning of the polymer shield over the CNTs facilitates the movement of charge carriers in the localized domains of the polyurethane network within the film [22], manifesting a promising light induced electrical photo-response and switching characteristics. Jintoku et al [9] reported on SWCNT, graphene hybrid films of having better absorbance by controlling the intensity and irradiation time of UV light and are switchable after visible light irradiation and thermal treatment, making them potential candidates for optoelectronic devices and sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, carbon nanomaterials have shown promising photo responsive behaviour using white light (WL) as a stimuli which is readily available and is a spontaneous choice for many applications owing to its wide spectral range. Photoactive structural forms of carbon, for example functionalized SWCNTs and graphene with azobenzene can induce switching of electrical conductivity when irradiated by UV and visible light, showcasing potential utility in sensors, memory and energy storage devices [9], [10], [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The light-induced switching of SWCNTs and AB-based photoresponsive dispersant 22 is shown in Figure 5e. [117] The 22-SWCNT hybrid was obtained by a wet-coating method from a dispersed 22-SWCNT solution. A 22-SWCNT hybrid film exhibited switching in both electrical conductivity and near-infrared (NIR) absorbance upon UV/Vis irradiation.…”
Section: Non-covalent Approachesmentioning
confidence: 99%
“…The simplest yet most effective approach to modulating cold crystallization behavior is to incorporate an additive to the host. In general, the crystallization of a system with a noninteracting additive remains unaltered, where each component excludes the other. , On the other hand, when moderate interactions are present between components, the crystallization process can be notably modified as seen in the examples of a hydrazide compound and poly­(butylene succinate). , Given that the azobenzene moiety and the imidazolium ring of 1 can interact through π–π interactions, we selected a tubular π-conjugated polymer CNT as the additive. , Furthermore, CNT is an ideal additive expected to enhance the thermophysical properties of 1 due to its good thermal conductivity, small heat capacity, and absence of phase transition within the temperature range of interest. , …”
Section: Introductionmentioning
confidence: 99%